Characterization of Phenol Degrading Bacteria from Buntal Lake of Central Kalimantan - Nursaadah .; Dwi Andreas Santosa; Maggy T Suhartono (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2000)
Three bacterial isolates (ICBB 1168, ICBB 1169, ICBB 1170), being capable to utilizing phenol as sole carbon and energy source, were isolated from Buntal Lake of Central Kalimantan. Growth of all isolates were optimum at 37OC. Optimum pH for growth and phenol degradation of ICBB 1168, lCBB 1169, and ICBB 1170 were 7-8, 6, and 6-7, respectively. Among the isolates, ICBB 1170 showed best phenol degrading activity. ICBB 1170 able to degrade 16 mM phenol to 0.71 mM in 4days. Phenol degradation ability of ICBB 1170 could be increased by adding 0.01-0.1% yeast extract. Addition of 0.05-0.1% glucose in medium inhibited phenol degradation by ICBB 1170. Cell-free extracts of ICBB 1170 had specific activity 2.92 Ulmg. Degradation of benzoate by ICBB 1170 wasstudied. However, the ability to degrade phenol were higher than that of benzoate.